2020
DOI: 10.1242/bio.052308
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule assembly and pole coalescence: early steps in C. elegans oocyte meiosis I spindle assembly

Abstract: How oocytes assemble bipolar meiotic spindles in the absence of centrosomes as microtubule organizing centers remains poorly understood. We have used live cell imaging in Caenorhabditis elegans to investigate requirements for the nuclear lamina and for conserved regulators of microtubule dynamics during oocyte meiosis I spindle assembly, assessing these requirements with respect to recently identified spindle assembly steps. We show that the nuclear lamina is required for microtubule bundles to form a peripher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
69
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(86 citation statements)
references
References 44 publications
17
69
0
Order By: Relevance
“…In contrast, 50% of zyg-9(RNAi) embryos in the +1 position contained multipolar oocyte spindles while only 2% contained bipolar spindles, with the rest progressing to anaphase (Figure 1 – figure supplement 1D). These findings suggest that ZYG-9 is required for stable pole coalescence during acentrosomal spindle assembly, confirming the findings of a recent study (Chuang et al, 2020).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In contrast, 50% of zyg-9(RNAi) embryos in the +1 position contained multipolar oocyte spindles while only 2% contained bipolar spindles, with the rest progressing to anaphase (Figure 1 – figure supplement 1D). These findings suggest that ZYG-9 is required for stable pole coalescence during acentrosomal spindle assembly, confirming the findings of a recent study (Chuang et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…To confirm that degron::GFP:ZYG-9 retained its normal localization, we performed live imaging of oocytes and found that ZYG-9 begins to associate with microtubules at the multipolar stage, becoming enriched at the poles and increasing in intensity as the bipolar spindle forms (Figure 1 – figure supplement 2A, Figure 1B and Video 2), consistent with recent work (Chuang et al, 2020). Fixed imaging comparing the localization of degron::GFP::ZYG-9 to the spindle pole protein ASPM-1 confirmed these findings (Figure 1C, Figure 1 – figure supplement 2B).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations